Enterprise innovation in developing countries: An evidence from Ethiopia - Megersa Debela Daksa; Molla Alemayehu Yismaw; Sisay Diriba Lemessa; Shemelis Kebede Hundie (Journal of Innovation and Entrepreneurship, 2018)
Enterprise innovation has gained the interest of development policymakers and scholars as the bases for the industrial development. This study comprehensively analyzes the drivers of enterprise innovation in developing countries. The study uses survey data to analyze the determinants of enterprise innovation in Ethiopia using a multivariate probit (MVP) model. For this study, enterprises were grouped into four categories: all-sized, large-sized, medium-sized, and micro- and small-sized enterprises. It appears that engagement in R & D, on-the-job training, and website ownership significantly determine enterprise innovation. This study, unlike previous studies, comprehensively analyzes drivers of innovation by considering enterprises in different sizes and all at the same time. This helps identify factors most relevant for enterprise innovation at all stage which help policymakers get focused on strategy development. Based on the findings, further emphasis on engagement in R & D would help enterprises to become innovative for all categories of enterprises. Furthermore, strengthening the available formal training and diversifying type of the training that is related to skills, knowledge, and techniques that help achieve the long-term objective of the enterprises are worth considering. Enterprises also need to subscribe to different sites that help learn more and access information.
Keywords: 650; Enterprise; Innovation; Determinants; Multivariate probit; Ethiopia